STUDI STRUKTUR EPIDERMIS DAUN Dasymaschalon blumei Finet & Ganep. (Annonaceae) DI JAWA DAN SUMATERA - Nurmawati, Subekti; Sulistiana, Susi (LPPM Universitas Terbuka, 2007)
Dasymaschalon blumei Finet & Gagnep. Is one of the species from the genus Dasymaschalon (Hook. F & Thomson) Dalla Torre & Harms which can be recognized from its peculiar moniliform fruits. It widespread in Java and Sumatera. An anatomical of leaves from herbarium specimens of D. blumei collected from Java and Sumatera has been carried out by using light microscope in Herbarium Bogoriense. The objectives of this study is to observe the leaves anatomy of D. blumei and to support the classification of  the species concept of D. blumei.  The specimens are divided into three categories based on the elevation, those were: specimens collected from < 50 m; 250 – 500 m,; and > 500 m of sea level. The result showed that from the epidermal section, the type of the stomata from the three categories were similar, and also the number and the index of the stomata. Variations however exists because of the environment factors.